Proceedings of RESANTILLAS IV and LABANTILLAS II: Veterinary diagnostic laboratory report - Guyana - Meeting of Directors of Veterinary Diagnostic Laboratories of the Caribbean-LABANTILLAS II Ogle, East Coast Demerara (Guyana) 8-10 Abr 1987. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2021)
The Veterinary Diagnostic Services have experienced mixed fortunes over recent times. While training for several staff personnel took place, two senior staff members - clinical pathologist - and the parasitologist - resigned. Fortunately, the pathologist is available on a part time basis and in-house training is being given to two recent graduates in these areas. Diagnostic techniques were imporved in several areas. The extremely short shelf-life of blood serum chemistry reagents received by the laboratory continues to be a problem. All bovine sera submitted to this laboratory were tested negative for Brucellosis. On the other hand, outbreaks of Chronic Respiratory Disease (CRD), a malabsorption syndrome and Newcastle Disease played havoc in the poultry industry resulting in severe losses. Other disease outbreaks investigated were a mysterious death syndrome in Kunchen ducklings, Paralytic Rabies in cattle, Bovine Leukosis, Dermal Lymphosarcoma, Canine Distemper and Thallium Sulphate poisoining of birds. Several research surveys are slated to take place in the immediate future